First report of ibrutinib in IgM-related amyloidosis: few responses, poor tolerability, and short survival - Pica, Tomas; Hegenbart, Ute; Maier, Bettina; Kimmich, Christoph; Schönland, Stefan (Blood, 2018)
TO THE EDITOR: Light-chain amyloidosis (AL) is a rare systemic protein deposition disorder that belongs to the group of plasma cell dyscrasias. Approximately 10% to 22% of cases are associated with symptomatic multiple myeloma or Waldenström macroglobulinemia (WM). The disease is characterized by